2019
DOI: 10.1080/01694243.2019.1595890
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically robust, electrically and thermally conductive graphene-based epoxy adhesives

Abstract: This study develops a facile approach to fabricate adhesives consists of epoxy and cost-effective graphene platelets (GnPs). Morphology, mechanical properties, electrical and thermal conductivity, and adhesive toughness of epoxy/GnP nanocomposite were investigated. Significant improvements in mechanical properties of epoxy/GnP nanocomposites were achieved at low GnP loading of merely 0.5 vol%; for example, Young's modulus, fracture toughness (K 1C) and energy release rate (G 1C) increased by 71%, 133% and 190%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 53 publications
3
38
0
Order By: Relevance
“…Graphene has attracted a great attention for fabrication of flexible electronics devices/sensors because of its outstanding properties such as ultra‐high toughness, high elasticity, high electron mobility, and transparency and high electrical conductivity . Compared with CNTs, graphene provide lower cost in fabrication in the epoxy composites . Graphene platelets (GnPs) have been introduced recently with enormous advantages for fabrication of flexible sensors, including great structural sturdiness, high C/O proportion resulting in immensely increased electrical conductivity, offering solid foundation for piezoresistive sensors, and cost‐effectiveness .…”
Section: Introductionmentioning
confidence: 99%
“…Graphene has attracted a great attention for fabrication of flexible electronics devices/sensors because of its outstanding properties such as ultra‐high toughness, high elasticity, high electron mobility, and transparency and high electrical conductivity . Compared with CNTs, graphene provide lower cost in fabrication in the epoxy composites . Graphene platelets (GnPs) have been introduced recently with enormous advantages for fabrication of flexible sensors, including great structural sturdiness, high C/O proportion resulting in immensely increased electrical conductivity, offering solid foundation for piezoresistive sensors, and cost‐effectiveness .…”
Section: Introductionmentioning
confidence: 99%
“…However, the strength of the epoxy‐based adhesive joints is low in comparison with bolted, riveted, and welded joints . Developing mechanically robust and electrically and thermally conductive adhesives is of great interest in many industries including electronics, aerospace, and automotive. Mechanical strength, and electrical and thermal properties of epoxy adhesives can be improved by the addition of carbon nanomaterials such as carbon nanotubes (CNTs) and graphene, owing to their excellent mechanical and physical properties, and their high aspect ratio …”
Section: Introductionmentioning
confidence: 99%
“…They are able to establish a percolation network at low nanoparticle contents, while enhancing the mechanical properties [7]. Meng et al [8] reached electrical percolation for epoxy/graphite nanoplatelets (GnP) at approximately 1.2 wt.% GnP, reaching a maximum electrical conductivity of 10 −3 S/m and thermal conductivity of 0.33 W/m•K at approximately 4 wt.% of GnP. Li et al reported a percolation threshold of 1.2 wt.% for epoxy/functionalized graphene composites [9].…”
Section: Introductionmentioning
confidence: 99%